Understanding desaturation/hydroxylation activity of castor stearoyl Δ9-Desaturase through rational mutagenesis - Tupec, Michal; Culka, Martin; Machara, Aleš; Macháček, Stanislav; Bím, Daniel; Svatoš, Aleš; Rulíšek, Lubomír; Pichová, Iva (Computational and structural biotechnology journal, 2022)
A recently proposed reaction mechanism of soluble Δ9 desaturase (Δ9D) allowed us to identify auxiliary residues His203, Asp101, Thr206 and Cys222 localized near the di-iron active site that are supposedly involved in the proton transfer (PT) to and from the active site. The PT, along with the electron transfer (ET), seems to be crucial for efficient desaturation. Thus, perturbing the major PT chains is expected to impair the native reaction and (potentially) amplify minor reaction channels, such as the substrate hydroxylation. To verify this hypothesis, we mutated the four residues mentioned above into their counterparts present in a soluble methane monooxygenase (sMMO), and determined the reaction products of mutants. We found that the mutations significantly promote residual monohydroxylation activities on stearoyl-CoA, often at the expense of native desaturation activity. The favored hydroxylation positions are C9, followed by C10 and C11. Reactions with unsaturated substrate, oleoyl-CoA, yield erythro-9,10-diol, cis-9,10-epoxide and a mixture of allylic alcohols. Additionally, using 9- and 11-hydroxystearoyl-CoA, we showed that the desaturation reaction can proceed only with the hydroxyl group at position C11, whereas the hydroxylation reaction is possible in both cases, i.e. with hydroxyl at position C9 or C11. Despite the fact that the overall outcome of hydroxylation is rather modest and that it is mostly the desaturation/hydroxylation ratio that is affected, our results broaden understanding of the origin of chemo- and stereoselectivity of the Δ9D and provide further insight into the catalytic action of the NHFe2 enzymes.
Keywords: Proton transfer; Desaturation; Δ9 desaturase; Reaction mechanism; Hydroxylation; Methane monooxygenase